Remember, You Are an Artist, Not a Scholar. Six Drawing Lessons by William Kentridge (diségno, 2021)
The extraordinary endeavour of William Kentridge is the testimony of an intense, many years and productive work that relates to the dynamics of a complexity located in the cultural and political context of belonging, so being able to interpret it means being confronted with a visual universe capable of reflecting a precise personal need, in privileging the medium of drawing and in the freedom to hybridize it with cinema and theatre (read more).